Wholesome Dwellings - Graham, Malcolm (Archaeopress, 2020)
This study by Malcolm Graham, a leading Oxford local historian for many years, provides a fascinating insight into post-war housing needs in Oxford, and how the modern city evolved away from the university buildings and college quadrangles for which the city is internationally renowned